Flux profile of graphene oxide based polymer membrane - Che Yahaya, Nur Atiqah (2018)
In this work, dead-end filtration method is used to determine the water flux of commercial ultrafiltration membrane which are MK membrane, BN membrane PZ membrane, and also graphene oxide membrane. Polymer membrane had been widely used in membrane bioreactor and other industrial purposes such as wastewater treatment. One of the characterization of polymer membrane is to study the flux profile of the membrane. It is expected that different flux profile will be obtained for different types of polymer membrane. Generally, membrane with high hydrophilicity will show the ultrafast flow of water across membrane and it is due to low friction generated between water and hydrophobic region of the membrane itself. From this research, BN membrane shows highest water flux (the highest peak) at 174.95 L/m₂.h.bar while the water flux for MK membrane (120.72 L/m₂.h.bar), PZ membrane (14.39 L/m₂.h.bar) and GO membrane (8.89 L/m₂.h.bar)